(untitled) (EAAE Joint Publishings, 2026)
This paper untangles the emerging need for a critical understanding of phygital design and phygital material by exploring its most definitive qualities in the context of a quasi-autonomous collaboration between human agency and the computer, here explored through the digital reinterpretation of traditional handicrafts belonging to the ethnic Chinese minority Bai from the northwestern province of Yunnan. A phygital fabrication workflow challenges experience-based standardized fabrication techniques by creating atypical results from a constant exchange between physical fabrication and digital simulation, consciously acknowledging the contributions of the machine. It suggests, moreover, a new way to inherit indigenous design as a deliberate collaboration with non- human agencies, reflects the anxiety of designers seeking new positions around digital design tools, and describes a workflow not wholly defined but nonetheless integral to contemporary design practice.